Cupping Therapy Digital Marketing Strategy at the Hamdalah Cupping Center, Makassar City - Alamsjah; Moh Rizki Mahda Putra; Rusni Hasni; Zalkha Soraya (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This research is about Digital Marketing Strategy for Cupping Therapy at the Hamdalah Cupping Center in Makassar City based on an analysis of strengths, weaknesses, opportunities and threats (SWOT analysis). The aim of this research is to Know the Digital Marketing Strategy for Cupping Therapy at the Hamdalah Cupping Center in Makassar City based on SWOT analysis. The research method used is qualitative with descriptive method based on SWOT analysis. The results showed that the internal and external factors showed the IFAS (Internal Factor Analysis Summary) matrix obtained a value of 2.70 and EFAS (External Factor Analysis Summary) obtained a value of 2.96 and a digital marketing strategy based on SWOT analysis is to carry out market development and service development, carry out repositioning and Implementing Undifferentiated Marketing